Evaluation of Berseem (Trifolium alexandrinum L.) Varieties for Fodder and Seed Production - Gupta, J J; Dey, A (Indian Journal of Animal Nutrition, 2019)
An experiment was laid to find out the feasibility of different varieties of berseem for simultaneous production of forage and seed so as to fulfil the household requirement of both forage and seed under crop-livestock farming system. Three varieties of berseem seeds viz. JHB-146, Wardan and Hybrid were sown in first week of November with seed rate of 20kg/ha in line with distance of 15cm. Fodder was harvested three and/or four times at 55, 90, 110 and/or 130 days of crop duration.Â Â Irrigation with top dressing of urea @60kg/ha was provided after each harvest. Finally crop was harvested at 160 days of crop duration to record the total biomass and seed yield. Maximum cumulative fodder yield(P<0.01) was recorded from Wardan variety irrespective of total numbers of cuttings. However, total biomass yield was increased after forth cut of fodder. Significantly(P<0.01) highest berseem seed yield was recorded in Wardan variety after third cut of fodder in March first week than JHB-146 and Hybrid berseem variety. However, seed yield was drastically reduced in forth cut of fodder in March last week. Hence, it is recommended to harvest berseem fodder only three times and then may be left for maximum seed yield. However, reasonably good seed yield can also be taken from Wardan berseem variety even after forth cut of fodder in March last week.Â